2021
DOI: 10.1051/e3sconf/202131601011
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z consumer’s preferences for online food ordering application: a study of gofood and grabfood

Abstract: Online food ordering applications have become widely used recently. Its popularity is getting higher, especially among Generation Z, which is known to be the most familiar generation with information technology applications. This study aims to examine the preferences of Generation Z consumers and the most considered factors in purchasing food product using Gofood and Grabfood online food ordering applications. An online survey of 100 generation Z respondents was carried out through the google form application.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Juni et al ( 2021) underscore the importance of perceived benefits as the most influential factor affecting customers' decisions to use online food delivery services, further emphasizing the crucial role of consumer preferences. Akhmadi et al (2021) found that trust, convenience, and promotions are the main factors influencing consumer preferences for specific online food ordering applications.…”
Section: Various Food Choicesmentioning
confidence: 99%
“…Juni et al ( 2021) underscore the importance of perceived benefits as the most influential factor affecting customers' decisions to use online food delivery services, further emphasizing the crucial role of consumer preferences. Akhmadi et al (2021) found that trust, convenience, and promotions are the main factors influencing consumer preferences for specific online food ordering applications.…”
Section: Various Food Choicesmentioning
confidence: 99%
“…Sekitar 109,4 triliun rupiah telah diraup Grab. Sedangkan Gojek memperoleh 98 triliun rupiah dengan kurang lebih 750 juta pesanan per bulan [3].…”
Section: Pendahuluanunclassified
“…In recent years, the food delivery industry has witnessed a remarkable transformation with the rise of online platforms, revolutionizing the way consumers satisfy their culinary desires (Li et al, 2020). Particularly among Generation Z, individuals born between the mid-1990s and early 2010s, online food delivery has become an increasingly popular option (Akhmadi et al, 2021;Yulius et al, 2022). This generation, having grown up in the digital age, is known for their techsavvy nature and propensity to embrace innovative solutions that streamline their daily lives (Dimitriou & Abouelgheit, 2019;Vancia et al, 2023).…”
Section: Introductionmentioning
confidence: 99%